Green and rapid synthesis of zirconium metal–organic frameworks via mechanochemistry: UiO-66 analog nanocrystals obtained in one hundred seconds. Issue 43 (8th May 2017) - Huang, Yi-Hao; Lo, Wei-Shang; Kuo, Yun-Wei; Chen, Wen-Jin; Lin, Chia-Her; Shieh, Fa-Kuen
Abstract : A UiO-66 analog was synthesized in 100 s via water-assisted grinding by the evaluation of linker solubility effects. Abstract : A UiO-66 analog was synthesized in 100 s using water-assisted grinding. The linker solubility suggested that tetrafluorobenzene-1, 4-dicarboxylic acid was the best linker. Zr–metal–organic framework nanocrystals displayed good topologies and hydrophobicities, and high water/thermal stabilities. The less amorphous complex led to higher porosities and pore volumes with a 60 min grinding time.